Protocol of the TREASURE study: Thoracic RadiothErapy with Atezolizumab in Small cell lUng canceR Extensive disease$da randomized, open-label, multicenter phase II trial - Bozorgmehr, Farastuk; Christopoulos, Petros; Chung, Inn; Cvetkovic, Jelena; Feißt, Manuel; Krisam, Johannes; Schneider, Marc; Heußel, Claus Peter; Kreuter, Michael; Müller, Daniel W.; Thomas, Michael; Rieken, Stefan (BMC cancer, 2022)
Recently, the combination of the programmed death-ligand 1 (PD-L1) inhibitor atezolizumab with first-line chemotherapy has demonstrated to improve outcome for patients with advanced small cell lung cancer (SCLC), leading to approval of this regimen. At the same time, accumulating (pre-)clinical data suggest synergisms of radiotherapy and immunotherapy via the radiation-mediated induction of anti-tumor immunogenicity. Combining the recent findings, the TREASURE trial aims at further enhancing response to upfront chemo-immunotherapy by the addition of thoracic radiotherapy (TRT).
Gesehen am 18.10.2022